Instruction Sequences with Indirect Jumps - J. A. Bergstra; C. A. Middelburg (Scientific Annals of Computer Science)
We study sequential programs that are instruction sequences with direct and indirect jump instructions. The intuition is that indirect jump instructions are jump instructions where the position of the instruction to jump to is the content of some memory cell.